PENGARUH SALINITAS TERHADAP KELULUSAN HIDUP DAN PERTUMBUHAN BENIH IKAN BAWAL AIR TAWAR, Colossoma macropomum - D. Djokosetiyanto; A. R. Wulandari; O. Carman (Jurnal Perikanan Universitas Gadjah Mada, 2008)
The aim of this study was to know the optimal salinity level on survival and growth rates of Colossoma macropomum on larvae rearing in different salinity media. The treatment tested with six different salinities were 0; 2; 4; 6; and 10 ‰. This study was conducted from May 15 to June 12, 2006. The experiment design was arranged in completely randoumizes design with six treatments and three replications. Stock density was 1 fish/l with mean initial body weight 0.48 ± 0.03 g and initial total body length 3.04 ± 0.18 cm. The result showed that the optimal salinities between 5.74 – 6.35 ‰, which was giving growth rates 9.31 % and survival rates 100 %. On minimum salinitiy media (0 ‰) showed growth rate 5.45 % and survival rate 19.17 %.